What should be done in patients diagnosed with xanthogranulomatous cholecystitis? Case-control study - Tolga Canbak; Aylin Acar; Hüseyin Kerem Tolan (İstanbul Kuzey Klinikleri, 2020)
OBJECTIVE: In this study, we aimed to compare development of complications, malignancy and confusion rates in the preliminary diagnosis in patients with xanthogranulomatous cholecystitis identified. METHODS: In this study, 2803 patients undergone cholecystectomy between January 2010 and December 2016 were retrospectively evaluated. Patients with xanthogranulomatous cholecystitis identified in the histopathological examination were classified as Group 1 and patients with cholelithiasis, cholecystitis, and malignancy detected were classified as Group 2. RESULTS: Forty-five patients with xanthogranulomatous cholecystitis were classified as group 1 and 2758 patients as group 2. of group 1, 18 were male and group 2 consisted of 2758 patients with 707 (26%) being male (p=0.04). In the ultrasonographic examination, the wall thickness was increased in 40 patients in Group 1 and 662 patients in Group 2 (p<0.0001). The operation was converted to the open type in 24 patients in Group 1 and 61 patients in Group 2 (p<0.0001). Five patients in Group 1 and 32 patients in Group 2 developed complications in the postoperative period (p<0.0001). CONCLUSION: Xanthogranulomatous cholecystitis should be considered for the differential diagnosis and the operation should be performed, especially by carefully exposing the anatomy in these patients.